Manifestations of Pediatric Appendicopathia Oxyurica. Issue 9 (September 2013) - Jordan, Mary M.; Sanders, Jennifer E.; Stallworth, Christina R.; Russell, Scott; Titus, Olivia; Hill, Jeanne G.; Cina, Obert A.
Enterobius vermicularis is a parasite that inhabits the human digestive tract. We present two pediatric patients with symptoms mimicking acute appendicitis who were found to have E. vermicularis infection. The first case is a 5-year-old female who presented with flank and abdominal pain associated with low-grade fever and anorexia. She had localized tenderness in the right lower quadrant and a leukocytosis with left shift. Intraoperative findings included a normal-appearing appendix, but ex vivo examination revealed Enterobius vermicularis. The second case is a 7-year-old female who presented with periumbilical abdominal pain, anorexia, and emesis. She had tenderness at McBurney's point, and ultrasound revealed a small echogenic focus within the appendix. Intraoperatively, the distal tip of the appendix appeared inflamed. Again, ex vivo examination revealed E. vermicularis. Enterobius vermicularis infection of the appendix can present with a clinical picture similar to acute appendicitis. In at-risk populations, it should be included in the differential diagnosis for children with right lower quadrant abdominal pain. Complete therapy requires treatment with mebendazole.